2016
DOI: 10.1002/wat2.1188
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms leading to potential impacts of shale gas development on groundwater quality

Abstract: The development of shale gas resources was made possible by the combination of horizontal drilling and high‐volume hydraulic fracturing (fracking). Environmental concerns have been raised relative to shale gas production, especially potential impacts on groundwater. Fluids related to unconventional oil and gas (O&G) operations contain chemical compounds that can impact groundwater quality. Such impacts can occur due to (1) the infiltration of surface contaminant releases, (2) failures of the integrity of O&G w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 61 publications
(187 reference statements)
1
26
0
Order By: Relevance
“…The most common technique to fracture lowpermeability rocks is hydraulic fracturing, which uses a mixture of water, proppants (generally sand) and chemical additives that are injected at high pressure, generally in horizontal wells in a variable number of individual stages or fracturing events. The advent of fracking technology has M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 caused much debate and concerns among scientists and the public on the environmental risks that these unconventional resources exploration and development activities pose, especially to groundwater quality (Lefebvre, 2017). For this reason, some jurisdictions such as New Brunswick and Nova Scotia (Canada) and New York (U.S.) decided to impose a moratorium on high-volume hydraulic fracturing, at least until the risks for drinking water resources are better defined and understood, and social acceptability is reached.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common technique to fracture lowpermeability rocks is hydraulic fracturing, which uses a mixture of water, proppants (generally sand) and chemical additives that are injected at high pressure, generally in horizontal wells in a variable number of individual stages or fracturing events. The advent of fracking technology has M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 caused much debate and concerns among scientists and the public on the environmental risks that these unconventional resources exploration and development activities pose, especially to groundwater quality (Lefebvre, 2017). For this reason, some jurisdictions such as New Brunswick and Nova Scotia (Canada) and New York (U.S.) decided to impose a moratorium on high-volume hydraulic fracturing, at least until the risks for drinking water resources are better defined and understood, and social acceptability is reached.…”
mentioning
confidence: 99%
“…Although fracturing has caused much public concern, it is now commonly accepted in the scientific community that the main risks to groundwater quality stem from: 1) the handling and treatment of drilling and fracking fluids as well as flowback water from the well, which can be accidentally spilled or otherwise stored in improperly sealed reservoirs at the surface Lefebvre, 2017), and 2) fluid migration from depths through improperly-cemented gas well casings Jackson et al, 2013b). The incidence of these two contamination pathways can be minimized through the implementation of better industry practices and stricter regulations (Dusseault and Jackson, 2014), and several jurisdictions are starting to implement monitoring programs for drinking water wells located within a certain distance of shale petroleum wells, in order to detect contamination coming from the well or from development-related activities in the immediate vicinity (e.g., Boyer et al, 2012, MDDELCC, 2017.…”
mentioning
confidence: 99%
“…Several biological processes consume or produce H + ions. Aerobic oxidation of methane tends to produce H + , decreasing pH, whereas anaerobic oxidation of methane tends to increase alkalinity and increase or maintain pH (e.g., Soetaert et al ; Lefebvre ), as shown in the following equations assuming mildly alkaline conditions. All processes have been described as occurring in groundwater, sometimes with considerable overlap: aerobic oxidation, nitrate reduction, iron reduction, and sulfate reduction (Islas‐Lima et al ; Amos et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…UOG extraction and fracking can affect groundwater quality and quantity, and aquifer integrity, in a number of ways (Esterhuyse et al, ; Gorski & Trenorden, ; Lefebvre, ). To limit these adverse effects on groundwater systems, certain aspects must be regulated during UOG extraction (Table ).…”
Section: Aspects That Must Be Regulated To Limit Adverse Effects On Gmentioning
confidence: 99%